ANALISIS PENGHITUNGAN KERUGIAN NEGARA DARI HASIL DUGAAN TINDAK PIDANA KORUPSI YANG DILAKUKAN OLEH PT. TIMAH (Tbk) - Zaskia Hanyfah; Agnes Oktapia; Mirtha Tirta P (INTELIGENSIA MEDIA, 2024)
Indonesia was shocked by the alleged corruption case amounting to hundreds of trillions of rupiah which shocked the public, and to this day there are still many questions about this case. This time the mining industry has become the object of criminal practices of corruption which are currently in the spotlight and polemic in Indonesia. PT. Timah (Tbk) is suspected of committing criminal acts of corruption with its illegal mining from 2015 to 2022 and causing state losses estimated at IDR 271 trillion. However, the first question that arises is where the figure for the country's losses came from. The method used in this research is normative juridical, namely by approaching rules, regulations, norms and articles related to the alleged PT Timah corruption case. This research aims to determine the calculation of total state losses of IDR. 271 trillion from the proceeds of PT Timah (Tbk)'s alleged illegal mining corruption practices. The results of this research show that the value of state losses from alleged corruption in illegal tin mining carried out by PT. Timah (Tbk) throughout the 2015-2022 period has caused losses of IDR. 271. 069,688,018,700, where the value of the total loss comes from environmental (ecological) losses amounting to IDR. 157,832,395,501,025, environmental economic loss of IDR 60,276,600,800,000, and environmental restoration costs of IDR 6,257,249,726,025. Apart from that, there are also losses outside the forest area of around IDR. 47,703,441,991,650.